Concomitant cervical and transperineal parametrial high-dose-rate brachytherapy boost for locally advanced cervical cancer - Bailleux, Caroline; Falk, Alexander Tuan; Chand-Fouche, Marie-Eve; Gautier, Mathieu; Barranger, Emmanuel; Hannoun-Levi, Jean-Michel (Journal of Contemporary Brachytherapy, 2016)
Purpose: There is no consensus for parametrial boost technic while both transvaginal and transperineal approaches are discussed. A prototype was developed consisting of a perineal template, allowing transperineal needle insertion. This study analyzed acute toxicity of concomitant cervical and transperineal parametrial high-dose-rate brachytherapy (HDRB) boost for locally advanced cervical cancer. Material and methods: From 01.2011 to 12.2014, 33 patients (pts) presenting a locally advanced cervical cancer with parametrial invasion were treated. After the first course of external beam radiation therapy with cisplatinum, HDRB was performed combining endocavitary and interstitial technique for cervical and parametrial disease. Post-operative delineation (CTV, bladder, rectum, sigmoid) and planification were based on CT-scan/MRI. HDRB was delivered in 3-5 fractions over 2-3 consecutive days. Acute toxicities occurring within 6 months after HDRB were retrospectively reviewed. Results: Median age was 56.4 years (27-79). Clinical stages were: T2b = 23 pts (69.7%), T3a = 1 pt (3%), T3b = 6 pts (18.2%), and T4a = 3 pts (9.1%). Median HDRB prescribed dose was 21 Gy (21-27). Median CTVCT (16 pts) and HR-CTV MRI (17 pts) were 52.6 cc (28.5-74.3), 31.9 cc (17.1-58), respectively. Median EQD2αβ10 for D90CTV and D90HR-CTV were 82.9 Gy (78.2-96.5), 84.8 Gy (80.6-91.4), respectively. Median EQD2αβ3 (CT/MRI) for D2cc bladder, rectum and sigmoid were 75.5 Gy (66.6-90.9), 64.4 Gy (51.9-77.4), and 60.4 Gy (50.9-81.1), respectively. Median follow-up was 14 months (ranged 6-51). Among the 24 pts with MFU = 24 months, 2-year LRFS rate, RRFS, and OS were 86.8%, 88.8%, and 94.1%, respectively. The rates of acute genitourinary and gastrointestinal toxicities were 36% (G1 dysuria = 8 pts, G2 infection = 2 pt, G3 infection = 2 pts), and 27% (G1 diarrhea = 9 pts), respectively. One patient presented vaginal bleeding at the time of applicator withdrawal (G3-blood transfusion); no bleeding was observed due to the parametrial implant. Conclusions : Concomitant cervical and transperineal parametrial HDRB boost for locally advanced cervical cancer appears feasible and safe with no specific acute toxicity compare to cervical HDRB alone. Longer follow-up and larger patient cohort will be needed.